Six Months of Daily High-Dose Xylitol in High-Risk Schoolchildren: A Randomized Clinical Trial on Plaque pH and Salivary Mutans Streptococci - Campus, G.; Cagetti, M.G.; Sacco, G.; Solinas, G.; Mastroberardino, S.; Lingström, P. (Caries research, 2009)
A randomized clinical trial was designed to evaluate the effect of daily high-dose xylitol chewing gum on plaque pH and salivary mutans streptococci (MS) in a sample of schoolchildren at high risk of caries. The study was performed on 204 subjects (acceptance rate 88.3%). Inclusion criteria were: >1 and <4 carious lesions, and a salivary MS concentration >10 5 CFU/ml. Subjects were randomly assigned to the xylitol or control group. Study design included one examination at baseline (t₀), one after 3 months of chewing (t 1 ), one after 6 months of chewing (t 2 ) and the last 3 months after the end of chewing period (t 3 ). Plaque pH was assessed using the MicroTouch technique, following a sucrose challenge. The area under the curve (AUC 5.7 and AUC 6.2 ) was recorded. Whole saliva was collected in sterile vials and MS CFU/ml were counted. Data were analysed using repeated-measures ANOVA. The main result was that plaque acidogenicity was reduced in both groups. The differences between treatments were statistically significant both for plaque pH and MS concentration; the interaction term for treatment and time was statistically significant (p < 0.01). At t 2 , the xylitol group children with a salivary MS concentration >10 5 and those with ≤10 5 showed significantly lower AUC 5.7 and AUC 6.2 values than the control group. These results suggest that the long-term use of high-dose non-sucrose chewing gums had beneficial effects on plaque pH, and that this effect was statistically greater when using xylitol chewing gums, both on plaque pH and MS salivary concentration.